The evolution of the provision of public services In the information society (Revista Direito em Debate, 2022)
This article aims to analyze how the evolution of the provision of public services has significantly impacted the lives of citizens, in the most diverse ways, aiming to build how this perception goes through the construction of democracy itself and digital democracy, which expanded the ways in which society interacts with technology in the Democratic and Social Rule of Law. We approach how the social function of the state evolved from the most philosophical perspectives until the arrival of digital needs that surround us daily. Finally, we verify how the State has expanded the use of technologies at the service of society and what are the needs and challenges imposed on it so that the citizens' participatory democracy can prevail.